SUBSTITUSI SEMEN DENGAN CAMPURAN ABU SEKAM DAN KAPUR PADA CAMPURAN BETON - Martini Martini (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Rice husk ash from waste rice processing, is often interpreted as a waste material / waste materials from the processing of agricultural products. Waste material surrounding environment can be used as an additive to concrete, for example rice husk ash. Several previous studies stating rice husk ash contains elements that are useful in increasing the compressive strength of the concrete. In addition, the use of rice husk ash will reduce the porosity of concrete and improve adhesion between the cement paste with aggregate.Create variation 5 (five) draft specimen mix husk ash, lime and cement. The first test specimen, substitution husk ash content of 0%, the second test specimen substitution husk ash content of 2.5%; The third test specimen substitution husk ash content of 5%, the test object fourth substitution husk ash content of 7.5% and the test object fifth substitution husk ash content of 10%.Concrete compressive strength test results for a variety husk ash 0% obtained the compressive strength of 149 kg / cm2, husk ash content of 2.5% obtained value of the compressive strength of 108 kg / cm2, 5% rice husk ash content values obtained compressive strength of 158 kg / cm2 , ash content of 7.5% husk obtained Nikai compressive strength of 141 kg / cm2, husk ash content of 10% obtained value of the compressive strength of 178 kg / cm2.Keyword : concrete, rice husk ash, compressive strength